Their C-termini divide Brassica rapa FT-like proteins into FD-interacting and FD-independent proteins that have different effects on the floral transition - Lee, Areum; Jung, Haemyeong; Park, Hyun Ji; Jo, Seung Hee; Jung, Min; Kim, Youn-Sung; Cho, Hye Sun (Frontiers in Plant Science, 2023)
Members of the FLOWERING LOCUS T (FT)-like clade of phosphatidylethanolamine-binding proteins (PEBPs) induce flowering by associating with the basic leucine zipper (bZIP) transcription factor FD and forming regulatory complexes in angiosperm species. However, the molecular mechanism of the FT–FD heterocomplex in Chinese cabbage (Brassica rapa ssp. pekinensis) is unknown. In this study, we identified 12 BrPEBP genes and focused our functional analysis on four BrFT-like genes by overexpressing them individually in an FT loss-of-function mutant in Arabidopsis thaliana. We determined that BrFT1 and BrFT2 promote flowering by upregulating the expression of floral meristem identity genes, whereas BrTSF and BrBFT, although close in sequence to their Arabidopsis counterparts, had no clear effect on flowering in either long- or short-day photoperiods. We also simultaneously genetically inactivated BrFT1 and BrFT2 in Chinese cabbage using CRISPR/Cas9-mediated genome editing, which revealed that BrFT1 and BrFT2 may play key roles in inflorescence organogenesis as well as in the transition to flowering. We show that BrFT-like proteins, except for BrTSF, are functionally divided into FD interactors and non-interactors based on the presence of three specific amino acids in their C termini, as evidenced by the observed interconversion when these amino acids are mutated. Overall, this study reveals that although BrFT-like homologs are conserved, they may have evolved to exert functionally diverse functions in flowering via their potential to be associated with FD or independently from FD in Brassica rapa.